The Borneo Islamic Heritage and The Significance of Idahan Jawi Manuscript - Suraya Sintang; Rosdiana Onga; Siti Aidah Hj Lukin; Asmady Idris (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
Borneo Island is the third largest island in the world, rich in natural resources, biodiversity and cultural diversity. The uniqueness of Borneo is that it is home to three countries; Malaysia, Indonesia and Brunei Darussalam, each with their own valuable cultural heritage. One of the unique aspects of the Borneo archipelago is the shared wealth of civilizations derived from the dissemination of Islam. Treasures known as the “Borneo Islamic Heritage